Customer’s perception towards airline industries due to disappearance of MH370 - Md Hatta, Hazirah (2012)
Kenwood Electronics Technologies (M) Sdn Bhd is one electronics manufacturing company that is actively producing car audio and multimedia until was an attractive places to be assessed over. The unique manpower profile making the company somehow attractive. The career maturity and career development is something unique to be study over. The career success would likely be assessed against the age and gender. The research made over 118 respondents has been asked to fill in the survey. They were choosing randomly. Data collection used was primary and secondary data. SPSS or statistical package for social science software V.19 was use to tabulating the data and finding. Generally, the data collected is calculated and tabulated and there is 4 hypothesis need to be tested. Based from the finding, it can be said that age does not relatively have any significant effect over the data. But, as gender is, there is somehow a relative correlation a little bit. The researchers also did some recommendations on how to improve the situation gaps.